Edition Of The Interpretation Of Al-Waraqat (Written By Al-Juwayni (Died 478 Ah) From the beginning of the manuscript to the end of the articles of aleumum The Interpreter Is Yusuf Ibn Al-Hasan Ibn Mahmud Tabrizi (Journal of Human Sciences, 2021)
This research is an edition of the interpretation of Al-Waraqat (written by Al-Juwayni (Died 478 AH);. The interpreter is Yusuf ibn Al-Hasan ibn Mahmud Tabrizi (Died  804 AH) The research included an introduction containing: the significance of the study, the reasons for choosing the above-mentioned manuscript, and the research proposal, which was as follows:The first section: The study. It included two chapters:The first chapter: A brief biography about the writer (Al-Juwayni) and the interpreter (Tabrizi).The second chapter: A brief summary about the interpretation.The second section: The manuscript's edition.It included: a preface describing the copy of the manuscript, the method followed in its edition, the edited text, and then come the references' index.